Improvement Chemical Properties of Oxisols and Rice Production with Humic Substances from Sub-bituminous Coal Indonesia - Herviyanti Herviyanti; Gusnidar Gusnidar; M. Harianti; A. Maulana (AGRIVITA, Journal of Agricultural Science, 2019)
Humic Substances (HS) sources of  Sub-bituminous can be used as soil amandement. The purpose of this research was to examine the residual effects of HS combined with P-fertilizers and the method of  incubation to improve Oxisols fertility and rice production. The experiment consisted of 2 factors, including: 1) incubation methods (i.e. I1 = HS incubated 1 week, then incubation of P fertilizers 1 week; I2 = HS and P- fertilizers directly incubated into the soil  2 weeks; and I3 = HS and P-fertilizers mixed 1 week, then incubated to soil 1 week), and 2) residual effect of HS with P-fertilizers combinations (i.e. H1 = 800 ppm + 100%; H2 = 800 ppm + 75% R; H3 = 400 ppm + 100% R; and H4 = 400 ppm + 75% R). All treatment was compared to the tradition of fertilization by the local farmers and control. The results showed that the combination of residual effects (HS and P-fertilizers) with the incubation method decreased exchangeable Al, as consequently increased the available P in Oxisols. The HS addition increased the efficiency of P fertilizers up to 25%, as well as increased rice production in averaged 3.9 t/ha (i.e. treatment H4).